Bacterial etiologic agents causing neonatal sepsis and associated risk factors in Gondar, Northwest Ethiopia - Tsehaynesh G/eyesus; Feleke Moges; Setegn Eshetie; Biruk Yeshitela; Ebba Abate (BMC, 2017)
Abstract Background Neonatal sepsis is a blood stream infection which is seen in the first month of life of the neonate. Bacterial profile of neonatal septicemia is constantly changing thus, current knowledge on the patterns of bacterial isolates, its antibiotic resistance profile, and associated factors, are essential to design and implement appropriate interventions. Therefore, the aim of this study was to identify bacterial etiologic agents, their antimicrobial susceptibility pattern and associated risk factors of neonatal sepsis among neonates. Methods A cross- sectional study was conducted among neonates suspected to sepsis attending University of Gondar Hospital from September/2015 to May/2016. A total of 251 consecutive neonates with clinical sign and symptoms of sepsis were included in the study. Blood sample was collected and directly inoculated into Trypton soya broth bottle and incubated at 37 °C. After 24 h of incubation it was sub- cultured in to blood agar plate, chocolate agar plate, manitol salt agar and Macconkey. The bacterial pathogens and antimicrobial susceptibility tests were identified using standard microbiological methods. Bivariate and multivariate logistic regressions were used to identify possible associated risk factors. Prior to the study ethical clearance was obtained from the School of Biomedical and Laboratory Sciences, University of Gondar. Results Of the 251 study participants suspected of neonatal sepsis, 117 (46.6%) showed bacterial growths, of them 120 bacteria were isolated. Gram positive bacteria were commonly isolated 81 (67.5%).The commonly isolated bacterial species were S. aureus 49 (40.8%) followed by coagulase negative Staphylococci 26 (21.6%) and K. pneumoniae19 (15.8%). The overall rate of multidrug resistance isolates was 78 (65%: CI 95%: 56.7-72.5%). Multidrug resistant (MDR) among Gram positive and negative bacteria were 56 (69.1%) and 22 (56.4%), respectively. Independent risk factors for the occurrence of neonatal sepsis were; Apgar score < 7/5 min (Adjusted odds ratio [AOR] =0.5), birth weight < 1.5 kg (AOR = 12.37), birth weight, 1.5-2.5 kg (AOR = 2.6), gestational week <37 weeks (AOR = 9) and caesarian section delivery (AOR = 5.2). Conclusion The isolation rate of bacterial pathogens in neonatal sepsis was considerably high. In addition, nearly 70% of isolates were MDR strains. Low birth weight, low Apgar score, preterm delivery and caesarian section modes of delivery were associated risk factors. Therefore, appropriate antenatal care follow up, and health education should be encouraged, especially on the importance of natural way of delivery.